A Review of Aquafeed Attractants as a Guide for Aquaculture Industry - Thaleia N. Roda; Razieh Farzad; Michael S. Allen (EDIS)
The aquaculture industry can use feed attractants to improve the feed intake efficiency of various fish and shellfish species. These attractants can be used for improving fish growth and survival, particularly during the sensitive early-life phases when effective feeding is critical to survival. Thus, there is a need to review the types of attractants and their effectiveness in improving fish growth and survival. In this EDIS publication, we provided background information on how feed attractants work and provided the available list of feed attractants that have been used by industry.